Thank you for your service [compact disc, unabridged] - Finkel, David, 1955- (Macmillan Audio, 2013)
"In Thank You for Your Service, Finkel has ... embedded with some of the men of the 2-16--but this time he has done it at home, here in the States, after their deployments have ended. He is with them in their most intimate, painful, and hopeful moments as they try to recover, and in doing so, he creates an indelible, essential portrait of what life after war is like--not just for these soldiers, but for their wives, widows, children, and friends, and for the professionals who are truly trying, and to a great degree failing, to undo the damage that has been done" --